2019
DOI: 10.21685/1680-0826-2019-13-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Diatom assemblages of the brackish Bolshaya Samoroda River (Russia) studied via light microscopy and DNA metabarcoding

Abstract: Diatoms are highly diverse and widely spread aquatic photosynthetic protists. Studies of regional patterns of diatom diversity are substantial for understanding taxonomy and biogeography of diatoms, as well as for ecological perspectives and applied purposes. DNA barcoding is a modern approach, which can resolve many problems of diatoms identification and can provide valuable information about their diversity in different ecosystems. However, only few studies focused on diatom assemblages of brackish rivers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Compared to the previously reported data (Burkova, 2012(Burkova, , 2015Gorokhova & Zinchenko, 2014;Yatsenko-Stepanova et al, 2015;Selivanova et al, 2019) our study revealed new taxa for the algae flora of the saline Elton rivers. Thus, 18 taxa belonging to the phyla Chlorophyta (5), Ochrophyta (4), Euglenozoa (4), Cryptophyta (3), Haptophyta (1), Cyanobacteria (1) have been recorded in the Bolshaya Samoroda River for the first time.…”
Section: Resultssupporting
confidence: 48%
See 3 more Smart Citations
“…Compared to the previously reported data (Burkova, 2012(Burkova, , 2015Gorokhova & Zinchenko, 2014;Yatsenko-Stepanova et al, 2015;Selivanova et al, 2019) our study revealed new taxa for the algae flora of the saline Elton rivers. Thus, 18 taxa belonging to the phyla Chlorophyta (5), Ochrophyta (4), Euglenozoa (4), Cryptophyta (3), Haptophyta (1), Cyanobacteria (1) have been recorded in the Bolshaya Samoroda River for the first time.…”
Section: Resultssupporting
confidence: 48%
“…On the other hand, the LM method is also not devoid of error. The diatomic analysis could take into account the forms represented by frustules of dead diatoms, which, due to their siliceous composition, can be retained for a long time in the reservoir (Rivera et al, 2018b;Selivanova et al, 2019). This can be confirmed by the fact that, for example, Navicula sp.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For this reason, a great effort has recently been directed to developing faster and less cumbersome identification methods and metrics. These are mainly based either on DNA metabarcoding or a combination of diatom imaging acquisition and deep learning methods [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. While these alternatives show promising results and take advantage of state-of-the-art sequencing and imaging methods, they are still laborious and quite expensive, which limits their application to routine monitoring of water quality.…”
Section: Introductionmentioning
confidence: 99%